The motives for seeking dental health services in a sample of children attending a College of Dentistry Erbil, Iraq. - Alla Mahmud Mustafa,; Heran Ibrahim Hassan; Fighan Jalal Huseen (Erbil Dental Journal)
Background and Objectives: The chief complaints of the patients are essential components, being useful for several reasons, including monitoring of oral health services and measuring the effectiveness of the oral health awareness programs. The objective of the study was to explore the common chief complaints of patients seeking treatment and distribution of cases according to the demographic data among patients attending a dental college in Erbil, Iraq. Patients and methods: The age, gender, and the chief complaints or the main reason for the visit were recorded for each consecutive patient of a total of 1233 patients who visited the oral hygiene clinics in the College of Dentistry at Hawler Medical University (Erbil city, Iraq), from October 2016 to June 2017 were recruited. Patients at the age of 3 - 14 years old. The chi-square test was used to find any statistical association between the variables. P value of less than 0.01 was considered statistically significant. Results: The pain was found to be the most common chief complaint reported by 51.1% of the patients. Followed by oral hygiene reported by 26%, among which 658 (53.4%) were males and 575 (46.6%) were females. When the age groups were considered separately, “toothache” or pain was the most common chief complaints reported by all ages except for the <5 years’ group patients for whom that oral hygiene was the most common chief complaint. In the age group of 10-14 years, in addition to pain and oral hygiene, significantly more subjects complained of orthodontic treatment need. Conclusion: Chief complaints denote the demand for dental care and thus, helps in proper planning of the public dental health care system. So the reason for dental visit varies across different age groups and to some extent, gender differences was a considering issue.